2021
DOI: 10.1515/jom-2021-0125
|View full text |Cite
|
Sign up to set email alerts
|

Mini-medical school programs decrease perceived barriers of pursuing medical careers among underrepresented minority high school students

Abstract: Context The percent of underrepresented minority (URM) students who apply to medical school has changed minimally in the past 40 years. Due to the lack of URM applicants, the consequent matriculation of URMs is grossly disproportionate from their percent representation of the US population. Increasing diversity among medical students and physicians has previously been identified as essential to decreasing healthcare disparities among US minorities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…To provide continued motivation to carry on with their pursuit of medical school, URiM and marginalized applicants rely on social support systems and mentoring ( Afghani et al, 2013 ; Acheampong et al, 2019 ; Abdulrazzak et al, 2021 ; Roche et al, 2021b ). For some students, in the face of adversity and stress, connecting with others decreased the negative effects and helped them stay motivated ( Morgan Consoli et al, 2015 ; Acheampong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…To provide continued motivation to carry on with their pursuit of medical school, URiM and marginalized applicants rely on social support systems and mentoring ( Afghani et al, 2013 ; Acheampong et al, 2019 ; Abdulrazzak et al, 2021 ; Roche et al, 2021b ). For some students, in the face of adversity and stress, connecting with others decreased the negative effects and helped them stay motivated ( Morgan Consoli et al, 2015 ; Acheampong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that ICMU increases undergraduate students' interest in UNC SOM, recruiting undergraduate students from underrepresented backgrounds for the ICMU course may advance UNC SOM's commitment to diversity and inclusion. One study found that the curriculum exposure in mini-medical school programs helped mitigate the perceived barrier of lack of guidance/role models [28]. ICMU may function similarly as undergraduate students build connections with medical students and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…URMs comprise only 8% through 13% of medical school matriculants 22,23 ; among medical students, Hispanics are underrepresented by 70% relative to the age-adjusted US population, Black males by 60%, and Black females by 40%. 24,25 Future research could investigate whether intentional recruitment and support of URM scribes leads to higher numbers of URM matriculants or whether scribe placement in critical shortage specialties (eg, family medicine) or underserved clinical settings (eg, rural) leads to higher numbers of students interested in those careers. Postbaccalaureate scribing programs may serve as pipeline development for prehealth students and may help increase the diversity of the future health care workforce.…”
Section: Discussionmentioning
confidence: 99%